Hospitalidade no trabalho dos comissários de voo: aproximações teóricas na perspectiva do cuidado - Silva, Aline Neves da (My University, 2022)
This study addresses hospitality in the work of flight attendants, aiming to establish theoretical-analytical connections between hospitality and the professional activity of flight attendants in the perspective of care. In this sense, this research of qualitative nature and hermeneutic approach is predominantly theoretical and documentary. Methodologically, besides the interpretative outlook provided by the hermeneutic approach, we also use analytical theories of the discourse, especially Bakhtin's theory that consider the historical, social, and cultural context for textual interpretation. Theoretically, regarding the reflections on hospitality, this research deals with this concept based on two trends: the trend of the gift and social bounds (CAMARGO, 2004, 2006, 2007, 2008, 2015; DERRIDA, 2003; MAUSS, 2003; PERAZZOLO et al., 2016; PERAZZOLO; PEREIRA; SANTOS, 2014; PERAZZOLO; SANTOS; PEREIRA, 2013), and the commercial trend (LASHLEY, 2004; LOCKWOOD; JONES, 2004). Nevertheless, the core of the research is on the intersections between both domains. In this sense, the reflections of Camargo (2013) and Gotman (2009, 2019) also contribute to understand the role of hospitality in flight attendants' work. As a result, we can state that care, even with the historical changes in this profession, is a path for the hospitality offered to airline customers, even though flight attendants by their contractual law have to zeal for the safety of customers. Thus, care emerges as a contractual law but goes beyond it: it can be understood as an intrinsic quality of flight attendant's job because there is always the possibility of "something more" in the hospitality offered by force of law. [resumo fornecido pelo autor]
O presente estudo aborda a hospitalidade no trabalho de comissários de voo, objetivando estabelecer aproximações teórico-analíticas entre hospitalidade e atividade profissional do comissário na perspectiva do cuidado. Nesse sentido, a pesquisa, de natureza qualitativa e de abordagem hermenêutica, é de cunho predominantemente teórico e documental. Metodologicamente, além da possibilidade interpretativa proposta pela abordagem hermenêutica, aproxima-se de teorias analíticas do discurso, em especial da bakhtiniana, que considera o contexto histórico, social e cultural para a compreensão dos textos. Teoricamente, esta pesquisa, no que tange às reflexões sobre hospitalidade, aprofunda o conceito a partir de duas vertentes: a vertente da dádiva e dos laços sociais (CAMARGO, 2004, 2006, 2007, 2008, 2015; DERRIDA, 2003; MAUSS, 2003; PERAZZOLO et al., 2016; PERAZZOLO; PEREIRA; SANTOS, 2014; PERAZZOLO; SANTOS; PEREIRA, 2013) e a vertente comercial (LASHLEY, 2004; LOCKWOOD; JONES, 2004). Entretanto, o cerne da pesquisa consiste no aprofundamento das intersecções entre esses dois domínios. Nesse sentido, as reflexões de Camargo (2013) e de Gotman (2009, 2019) também contribuem para o entendimento da hospitalidade presente no trabalho dos comissários. Como resultados, é possível afirmar que o cuidado, mesmo com as mudanças temporais ocorridas na profissão, constitui um caminho para a hospitalidade oferecida aos clientes das companhias aéreas, ainda que os comissários de voo, por força de lei contratual, zelem pela segurança daqueles que pagaram pelos serviços fornecidos. O cuidado surge, portanto, como força de lei contratual, mas não só; ele pode ser entendido como uma qualidade intrínseca da profissão de comissário de voo, pois há sempre a possibilidade de algo "a mais" na hospitalidade ofertada por força de lei. [resumo fornecido pelo autor]
Keywords: Hospitalidade; Comissário de bordo; Turismo; Hospitality; Flight attendant; Tourism